2019
DOI: 10.1155/2019/1231346
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of 1,25(OH)2D3 on TGF-β1 and miR-130b Expression in Streptozotocin-Induced Diabetic Nephropathy in Rats

Abstract: Objective To investigate the role of microRNA-130b in 1,25(OH)2D3 mediated improvement of renal fibrosis via transforming growth factor-beta 1 in a rat model of diabetic nephropathy (DN). Methods DN was induced in 30 rats by intraperitoneal injection of streptozotocin. These rats were randomly allocated to the DN group, TGF-β1 overexpression group (in situ injection of TGF-β1 lentivirus to kidney tissues), and TGF-β1 siRNA group (in situ injection of TGF-β1 siRNA lentivirus to kidney tissues). Rats with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Globally, there are 366 million DM patients and the numbers of new cases are predicted to double up by the year 2030. 1 Diabetic nephropathy (DN) is a common disorder that occurs because of both type 1 and type 2 DM and affects DM-associated mortality drastically. It is also responsible for renal dysfunction in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there are 366 million DM patients and the numbers of new cases are predicted to double up by the year 2030. 1 Diabetic nephropathy (DN) is a common disorder that occurs because of both type 1 and type 2 DM and affects DM-associated mortality drastically. It is also responsible for renal dysfunction in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that miR-130b reduced fat deposition in C57BL/6 mice, reversed glucose tolerance and improved high-fat diet-induced obesity ( 35 ). In addition, miR-130b has been shown to attenuate kidney fibrosis and damage induced by diabetes ( 36 ). The results of the present study indicated that the expression level of miR-130b was reduced in PC12 and hippocampal cells stimulated with high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 not only suppresses the inhibitory Smad7 of TGF-β signaling to promote fibrosis (Zhong et al, 2013;Wang et al, 2014) but also targeting the Sprouty (SPRY) to activate the Ras/MEK/ERK signaling to activate fibrogenesis of TGF-β signaling (Xu et al, 2014). In addition, miR-21 also exerts profibrotic and pro-inflammatory Anti/pro-fibrosis (Kato et al, 2007;Chung et al, 2010;Krupa et al, 2010;Kato et al, 2011b;Putta et al, 2012;Deshpande et al, 2013;Ma et al, 2016;Liu et al, 2018) (Zhong et al, 2011;Wang et al, 2013;Zhong et al, 2013;Wang et al, 2014;Lai et al, 2015;Mcclelland et al, 2015;Kölling et al, 2017;Chen et al, 2018) Pro-inflammation miR-27a SFRP1; PRKAA2; PPARγ Pro-fibrosis (Hou et al, 2016;Wu et al, 2018b;Shi et al, 2020) miR-130b TGF-β1; Smad2/3; Smad4 (Castro et al, 2014;Lv et al, 2015;Liu et al, 2019b;Ma et al, 2019b) effects by targeting PTEN, tissue inhibitor of matrix metalloproteinases (TIMPs), and other molecules, as shown in Table 3.…”
Section: Tgf-β/smad-dependent Mirnas In Renal Fibrosis and Inflammation In Dkdmentioning
confidence: 99%